Strategi Retorika Mahasiswa Berbasis Tradisi Budaya Makassar dalam Pembelajaran Bahasa dan Sastra - Dedi Gunawan Saputra; Filawati Filawati; Nur Hasbi; Rahmi Mardatillah; Ahmad Rizal Abdullah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to (1) identify and describe the forms of rhetorical strategies used by students in language and literature learning, and (2) analyze the reflection and implementation of elements of Makassar cultural traditions in these rhetorical strategies. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through direct observation of the learning process and in-depth interviews with students as research subjects. The data obtained are analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that students apply several main rhetorical strategies, such as the use of metaphors, similes, symbolic expressions, and local idioms that represent the values ​​of siri' na pacce, namely the concepts of self-esteem, solidarity, and empathy in Makassar culture. These culture-based rhetorical strategies are proven to be able to increase the effectiveness of academic communication, enrich language expression, and strengthen students' awareness and understanding of local cultural identity in the context of language and literature learning in higher education.